Financing agricultural activities in Afghanistan: a proposed salam-based crowdfunding structure - Buerhan Saiti; Muhibullah Afghan; Nazrul Hazizi Noordin (ISRA International Journal of Islamic Finance, 2018)
Purpose: This study aims to explore the potentials of adopting salam-based crowdfunding for financing the agricultural sector in Afghanistan. Design/methodology/approach: It adopts a triangulation approach, consisting of a number of methods used in gathering relevant information about Afghanistan's agricultural sector, the concept of crowdfunding and salam (forward sale) contract. These methods include library research, reviewing documents provided by Afghanistan's banks and semi-structured interviews with Islamic finance experts. Findings: This study finds that salam-based crowdfunding is a viable Sharīʿah-compliant investment platform, which may offer some advantages for both potential investors and farmers or entrepreneurs. Originality/value: The novelty of this paper lies in the proposed structure of salam-based crowdfunding.
Keywords: 330; Afghanistan; Crowd-funding; Islamic social finance/Islamic finance; Salam